"The Agitator's Wife" (1894): the story behind James Connolly's lost play?. Issue 1 (2nd January 2019) - Dick, Maria-Daniella; Lusk, Kirsty; Maley, Willy
ABSTRACT: The centenary of the Easter Rising in 2016 and the 150th anniversary of James Connolly's birth in 2018 afford an ideal opportunity to reappraise this unique figure. Rightly renowned for his polemical journalism and political theory, Connolly is less celebrated for his creative writing. His 1916 play, Under Which Flag?, long considered lost, resurfaced fifty years ago without causing significant ripples in Irish literary circles, but interest in Connolly's role in the struggle for Irish independence continues to grow, and critics are becoming increasingly aware of the fusion of feminist and socialist thought that shaped his particular anti-imperialist agenda. In this context his creative writing takes on new significance. A second lost play of Connolly's, The Agitator's Wife, has never been found, but its discovery would surely deepen our understanding of this gifted radical thinker. In this essay we suggest that an anonymous short story bearing that very title, published in a short-lived Christian socialist journal of the 1890s, may be a crucial missing piece in solving the puzzle of Connolly's forgotten drama.